SYSTEMIC PERSPECTIVE OF WORK IN PROGRESS AND ON TIME DELIVERY IN AEROSPACE COMPOSITES MANUFACTURING COMPANY IN MALAYSIA (Journal of Technology and Operations Management, 2016)
This paper explaines the significance of managing work in progress (WIP) and its impact on the on time delivery from a systemic perspective in aerospace composite manufacturing company in Malaysia. Research was done within an aerospace composites manufacturing company in Malaysia. A total of four years of data collection on WIP was done and co-related to on time delivery in a linear relationship while applying TOC and RBV. Acknowledgement of WIP as one of critical resources that need to be managed systemically, resource based view (RBV) theory is refered to in explain WIP as a unique, valuable and rare resource that is systemically impacting the whole manufacturing flow. The theory of constraint (TOC) was used to explain the WIP management method through ‘pull’ and ‘push’ to create a continuous flow of products to meet the completion date. WIP is one of manufacturing resource systemically impacting the on time delivery.The way WIP is managed contributes a whole lot to the performance and it is critically important in an aerospace manufacturing industry due to its high operations cost. To stay competitiveness in the industry, it is very important that this expectation is met and continuously sustained. Both TOC and RBV theories are complementing each other from a systemic point of view to explain the significance influence of WIP towards the on time delivery in an aerospace composite manufacturing in Malaysia. This paper is originally based on a real, objective scenario and shall be another input to the aerospace composite manufacturing best practices particularly in managing WIP systemically to achieve the targeted on time delivery and to continuously stay competitive in the industry.